The Influence Of Long-Term Tangıble Asset’s Valuatıon On Fınancıal Indıcators: The Attıtude Of Shareholders And Credıtors - Lina Paliuliene (European Scientific Journal, ESJ, 2016)
In the article the long-term tangible asset’s valuation methods by the historical cost and the fair value are generalized, indicators that are analyzed by shareholders and creditors when assessing the company's financial condition are identified. For the research eight Lithuanian companies which apply different long-term tangible asset’s valuation methods were selected from two industries. The influence of long-term tangible asset’s valuation was explored by five relative indicators. It was determined that valuation method is associated with long-term tangible asset’s part in the total company's asset. When long-term tangible asset’s part in the total company’s asset constitutes less than 50 percent, the asset’s valuation method has no influence on the analyzed indicators. When long-term tangible asset’s part in the total asset constitutes more than 50 percent, the asset’s valuation method affects solvency and investment indicators. Long-term tangible asset’s valuation method does not affect profitability indicators, independent of long-term tangible asset’s part in the total asset.